Non-hydrophilic components from roots of Vietnamese ginseng (Panax vietnamensis Ha & Grushv.) - Nguyen, Thi Hoang Anh; Dang, Thi Ngan; Manh Dung, Doan; Nguyen, Thi Thanh Binh; Nguyen, Ngoc Hieu; Vu, Van Tuan; Nguyen, Huu Tung (Hue University Journal of Science: Natural Science, 2024)
Vietnamese ginseng is a precious medicinal herb and contains various ginsenosides as the main components. We studied the less polar constituents of the title ginseng and isolated falcarinol (1) and 20S-protopanaxatriol (4) for the first time, along with two common phytosterols: β-sitosterol (2) and daucosterol (3). Their structures were elucidated with nuclear magnetic resonance (NMR) and mass spectrometry (MS) spectra and compared with the literature data. Falcarinol was obtained from the non-polar portion of the crude residue, with a high content. The occurrence of 20S-protopanaxatriol becomes evidence for similar biosynthesis of ginsenoside in Panax spp. The obtained results contributed partly to the phytochemical database of Vietnamese ginseng and the Panax genus.